Adsorptive Removal of Phosphate from Water Using Zr (IV)-Loaded Spent Cation Exchange Resin - Paudyal, Hari; Inoue, Katsutoshi; Ohto, Keisuke; Kawakita, Hidetaka (Journal of Nepal Chemical Society, 2017)
Available with fulltext